EFFECTS OF CARBONATED DRINKS ON THE BODY - Najibuloyev Zuhruriddin Jumakulovich; Abdullayev Tohir Khamzayevich; Gayratov Bekzod Shukhratovich; Azimov Sulaymon Lochinovich; Xolmurodova Dilafruz Quvvatovna (Web of Journals Publishing, 2024)
Gasification — 1) saturation of mineral waters, fruit juices, kvass, beer and champagne with carbon dioxide (SO2) gas. Gas gives the drinks a refreshing effect, improves their absorption into the body, and makes the taste pleasant. There are two methods of gasification: gasification directly into liquids (liquids, fruit juices, mineral waters; special equipment is used for this. 0.3-0.5 mg of carbonic acid is added to 1 liter of drink); saturation of drinks due to gas released during fermentation (liquid, champagne, beer, kvass); 2) fuels Gas - coal, fuel oil, peat, wood, slanes, etc. obtaining generator gas from fuels. Using a gas generator, fuel is oxidized with air or water vapor at a high temperature. If gasification is done using a steam-oxygen mixture under pressure, city gas containing up to 15% methane is produced. A by-product, generator tar, is also obtained from the gas.
Keywords: mineral waters, fruit juices, SO2, liquid, champagne, beer, kvass, fuel oil, generator tar, wood.